Valdosta State College Baseball, 1981 - Valdosta State University, Athletics Department (Valdosta State University, 1981)
Valdosta State College Baseball, 1981. Program.
Mickey Taylor; Greg Waits; Tim Russell; Mark Powell; Joe Mederos; Tom Roszell; Casey Fetherolf; Jay McDonough; Richie Johnson; John Keigher; Bobby Roche; David Raffensberger; Andy Keating; Leroy Dixon; Dennis Rich; Julio Navarro; Bud Drew; Jim Rod; Mark Schanback; Bob Polfcastro; Wayne Fugett;
Keywords: Athletics; Baseball